2013
DOI: 10.1149/2.029309jss
|View full text |Cite
|
Sign up to set email alerts
|

IR Emission Band and Multiple-Peak Structure in Photoluminescence Spectra of SnO2:Mn

Abstract: SnO2:Mn phosphor was synthesized by chemically etching metallic Sn and Mn shots in aqueous HNO3 solution. The synthesized phosphor was investigated by photoluminescence (PL), PL excitation spectroscopies, and PL decay time measurements. The PL spectra of SnO2:Mn exhibited a strong IR emission at ∼800 nm and green/red (G/R) emission. The G/R emission band was also observed in undoped SnO2. These emission bands were attributed to the Mn2+ (IR) and Sn2+ (G/R) ions in the SnO2 host, respectively. The IR emission b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In Fig. 7, the I PL value gradually increases with increasing T above ∼100 K. This phenomenon is very interesting and has also been previously observed in some phosphors, such as Ga 2 O 3 :Cr 3+ , 14 SnO 2 • H 2 O, 42 SnO 2 :Mn 2+ , 43 SnO 2 :Eu 3+ , 44,45 SnCl 2 , 46 MnF 2 , 47 CaCO 3 :Ce 3+ ,Mn 2+ , 48 K 2 SiF 6 :Mn 4+ , 49 BaSiF 6 :Mn 4+ , 50 and ZnSiF 6 • 6H 2 O:Mn 4+ . 51,52 An increase in the PL intensity with increasing T cannot be explained by the simple thermal quenching model of Eq.…”
Section: Resultssupporting
confidence: 80%
“…In Fig. 7, the I PL value gradually increases with increasing T above ∼100 K. This phenomenon is very interesting and has also been previously observed in some phosphors, such as Ga 2 O 3 :Cr 3+ , 14 SnO 2 • H 2 O, 42 SnO 2 :Mn 2+ , 43 SnO 2 :Eu 3+ , 44,45 SnCl 2 , 46 MnF 2 , 47 CaCO 3 :Ce 3+ ,Mn 2+ , 48 K 2 SiF 6 :Mn 4+ , 49 BaSiF 6 :Mn 4+ , 50 and ZnSiF 6 • 6H 2 O:Mn 4+ . 51,52 An increase in the PL intensity with increasing T cannot be explained by the simple thermal quenching model of Eq.…”
Section: Resultssupporting
confidence: 80%
“…A similar luminescence band has also been reported in a previous work where Cr doped SnO 2 microtubes were fabricated by a similar process carried out at higher temperature . Some other doped SnO 2 samples also show a near-infrared emission, as the Mn doped SnO 2 phosphors reported by Arai et al However, some authors have also reported a luminescence band at around 1.6 eV in undoped SnO 2 nanowires synthesized by a hydrothermal method, attributed in that case to high density of surface or defect states. Therefore, although further research is still required, the origin of this emission could be associated with defects characteristic from SnO 2 , the concentration of which, in our case, would be favored by the presence of Cr as a dopant.…”
Section: Resultsmentioning
confidence: 89%
“…5. [23][24][25][26] From Eqs. 3 and 4, we obtain an expression for the integrated PL intensity I PL (T) as…”
Section: Resultsmentioning
confidence: 99%